The Role of Silver Nanoparticles Against Amoxicillin/ Clavulanate-Induced Liver Damage in the Female Rats - Afyaa Sabah Nasir; Basheer Sadoon Taher (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current study was designed to evaluate the protective effect of silver nanoparticles against toxicityinduced by amoxicillin/clavulanate acid. Number of rats in the experiment are nine divided into three groupseach group has three rats. The first group is kept as control group and administrated normal saline, the secondis administered amoxicillin/clavulanate acid at dose 80 mg/kg and third group is administered amoxicillin/clavulanate acid at dose 80 mg/kg and silver nanoparticles at dose 50 mg/kg for 30 days. The results showsignificant increase (p<0.05) in the liver aminotransferase levels (AST, ALT and ALP), total protein andalbumin in addition significant increase (p<0.05) in the lipid profile total cholesterol TC, triglyceride TG,low density lipoprotein LDL, very low density lipoprotein VLDL and significant decrease (p<0.05) inthe high density lipoprotein HDL incompare with control group. In conclusion: silver nanoparticles hasbeneficial effectagainst side effects induced by amoxicillin/clavulanate acid in rats.